Bangladesh economy : evaluation and a research agenda - Rashid, Salim, 1949-; Bangladesh Institute of Development Studies (Dhaka, Bangladesh : University Press, 1995)
Contributed articles.
"This book has been published in collaboration with Bangladesh Institute of Development Studies, (BIDS) Dhaka"--T.p. verso.
Includes bibliographical references.
Keywords: Economics; Bangladesh -- Economic conditions; Bangladesh -- Economic policy; Bangladesh -- Rural conditions